Masculinity in German-Turkish Films - Onur Kemal Bazarkaya (Studien zur Deutschen Sprache und Literatur)
Since the mid-1990s, in social and cultural sciences it has been discussed to which extend masculinity is in crisis and how this is reflected in social processes as well as artistic works. Raewyn Connell’s concept of ‘hegemonic masculinity’, which has meanwhile become a theoretical classic, is central in this context. Regarding the German-Turkish film, the thesis of masculinity in crisis can be located particularly to the 2000s and 2010s. For this period, the (self)conscious reflection of transcultural positions and the naturalness, with which multicultural identity attributions are made, has a special significance; the second and third generation of immigrants doesn’t appear to have an essential understanding of culture. What drives their representatives is rather the individual search for their own lifestyle. It can be assumed that such searching movements are also extended to the negotiations of gender roles. The article will deal with the question of what this concretely means in terms of masculinity varieties implied in German-Turkish films – a subject that has so far been largely ignored in research. This will be realized on the basis of a serial of (subjectively) selected films, whose analysis is presenting a structural overview of the topic. The focus lies on four mutually impacting points: 1. state vs. milieu, 2. father vs. son, 3. Cain vs. Abel (the rivalry between brothers), and 4. man vs. woman. For the theoretical perspectivation of these oppositions various hypotheses from the Men’s Studies, which are attached to Connell’s concept of ‘hegemonic masculinity’, are applied.